EVALUASI PERCEPATAN PENYERAPAN ANGGARAN KEMENTERIAN DAN LEMBAGA - Sujai, Mahpud (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2012)
Government efforts to increase the people's welfare depend on the budget implementation. Currently, budgeting system has led to a performance-based budgeting in which the allocation should be based on the generated output.Effective implementation of the budget can be seen from the realization of the optimal absorption of the budget in order to accelerate economic growth. This paper analyzes the conditions and problems related to the absorption of the budget of the line ministries/agency. The methodology of this research used a qualitative descriptive analysis of the expenditure data realization of line ministries/agency and by regulatory review. This paper identifies three main factors that cause bottleneck of the absorption factor which area budget planning, bureaucratic factors, especially the mechanisms of administration and procurement as well as cultural factors, especially the budget discipline. This paper recommends a mechanism to improve planning and budgeting at the line ministries/agency, simplifying the procurement mechanism and the administrative mechanisms of the budget, and budget discipline. It is very important to do in order to optimalize the use of state budget for promoting economic growth to improve the welfare of the Indonesian people